Sphingomyelin organization is required for vesicle biogenesis at the Golgi complex - Durán, Juan M.; Sachsenheimer, Timo; Brügger, Britta; Wieland, Felix T. (The EMBO journal, 2012)
Sphingomyelin and cholesterol can assemble into domains and segregate from other lipids in the membranes. These domains are reported to function as platforms for protein transport and signalling. Do similar domains exist in the Golgi membranes and are they required for protein secretion? We tested this hypothesis by using d‐ceramide‐C6 to manipulate lipid homeostasis of the Golgi membranes. Lipidomics of the Golgi membranes isolated from d‐ceramide‐C6‐treated HeLa cells revealed an increase in the levels of C6‐sphingomyelin, C6‐glucosylceramide, and diacylglycerol. d‐ceramide‐C6 treatment in HeLa cells inhibited transport carrier formation at the Golgi membranes without affecting the fusion of incoming carriers. The defect in protein secretion as a result of d‐ceramide‐C6 treatment was alleviated by knockdown of the sphingomyelin synthases 1 and 2. C6‐sphingomyelin prevented liquid‐ordered domain formation in giant unilamellar vesicles and reduced the lipid order in the Golgi membranes of HeLa cells. These findings highlight the importance of a regulated production and organization of sphingomyelin in the biogenesis of transport carriers at the Golgi membranes.